A method for increasing 3D body scanning`s precision: Gryphon and consecutive scanning - Parker, C. J.; Gill, S.; Harwood, A.; Hayes, S. G.; Ahmed, M. (Ergonomics, 2022)
The fashion industry cannot use 3 D Body Scanning to create custom garment patterns because its measurements fail to meet ISO 20685:2010`s tolerances. To advance 3 D Body Scanning`s precision, we present Gryphon: an algorithm that removes the two most extreme measurements from five body scans; removing potentially erroneous data. We assess Gryphon`s precision against current industry practice, determine if consecutive and non-consecutive data capture influences precision, and determine 3 D Body Scanning`s inherent imprecision inherent. We analyse 97 participants over 121 industry-standard measurements for consecutive and non-consecutive data-capture through MANOVA statistical analysis. Under current industry practice, only one measurement meets ISO 20685. However, under Gryphon and consecutive scanning, 97.5% of measurements meet ISO 20685. We also prove that the body`s in-scan movement does not affect reliability. Ultimately, we offer the fashion industry, ergonomists, and practitioners an accessible method to increase 3 D Body Scanning`s precision at a level unavailable under previous methods.